Cashing out excellence - Austin, Robert D. 1962-; Hayes, Robert H.; Nolan, Richard L. (MIT Sloan Management Review, 2023)
Recent disruptive events like the pandemic and war in Europe have exposed businesses weakened by short-sighted leadership decisions, and many companies risk being unprepared for the new challenges that will inevitably emerge. The authors analyzed Southwest Airlines, Boeing, and GE to understand how and why successful companies sacrifice the business excellence they spent years building for near-term financial gains that ultimately harm investors, employees, and customers.
"Reprint 64437.". - Includes bibliographical references
Keywords: Business planning; Strategic planning; Planification stratégique